Estudios hacia la síntesis del núcleo heterocíclico del Sifonazol y Muscorida A vía reacción de Pummerer (2016)
Substituted Oxazoles are an important type oh heterocyclic compounds present in a variety of biologically significant products. Among these, Siphonazole and Muscoride have been previously researched both due to their biological and synthetic relevance. Hereby, an alternative synthetic route to these compounds starting from amino acids and using a previously in group developed Pummerer methodology to obtain the desired heterocyclic core is envisioned. Summing up, such route is studied in a simplified model, developing a methodology of oxidation-elimination for the procurement of the desired heterocyclic core.